Expansão rápida da maxila apoiada em mini-implantes: comparação entre diferentes diâmetros dos parafusos de ancoragem - Barbosa, Alex Juliano Prado (2010)
The present research aims to present an innovative rapid maxillary expansion methodology by the use of an expansor screw, i.e. Hyrax, adapted and supported by four mini implants, besides testing the different strength expansion resistance “in vitro” using mini implants of two different diameters as supporters. Ten testing bodies were used, all of them made metallic structure and 40 PCF (0,64g\cc) poliuretane artificial bone to which an expansor like Hyrax was adapted to each testing body , which by itself was sopported ans anchored on the four mini implants, all set in padronized positions on all testing body. These testing bodies were split equally into two groups, all mini implants were 10mm length, varying only their diameter: Group 1: 2,0 mm diameter; Group 2: 2,2 mm diameter. The testing bodies were then submitted to mechanical testing which simulated a palatine disjunction, aiming to avaliate the strength charge resistance, number of activations supported by the system and also verify the possible differences between the two groups. The results were picked through software Tesc 3.01 and were analysed statistically. It was found that: The system resisted to superior strength required to the palatine disjunction; The mini implants and the artificial bone were stable and did not damage the mechanical tests; Face to the generated strength charges during the tests, the resistance of the system as well as the quantity of gap in the expansor screws were statistically similar when comparing the two mini implants groups; The new system of maxilar disjunction showed its efficiency and feasibility through the “in vitro” tests.